Electromagnetic sinc Schell-Model Vortex Beams - Zhangrong Mei; Yuyan Wang; Yonghua Mao (IEEE Photonics Journal)
We introduce a new class of electromagnetic Schell-model source in which the cross-spectral density matrix possesses a sinc correlation function and a separable phase. The far-field radiation properties for the electromagnetic sinc Schell-model vortex beams generated by such source are investigated. It is shown that the far-field distributions of all statistical characteristics of such a beam possess vortex structure, depending on the topological charge and the correlation length of the source field.